ChemInform Abstract: Fluoroferrates with (dabcoH2)2+ or (dabcoH)+ Cations. Issue 32 (12th August 2014) - Darmograi, Ganna; Jouffret, Laurent; Hemon‐Ribaud, Annie; Leblanc, Marc; Dujardin, Gilles; Maisonneuve, Vincent; Lhoste, Jerome
Abstract: (H2 DABCO) [Fe III 2 F8 (H2 O)2 ] (I), (H2 DABCO)2 [Fe III 2 F10 ]·2H2 O (II), (HDABCO)4 [Fe III 2 F10 ]·10H2 O (III), and (HFDABCO)[(Fe II (H2 O)6 ) (Fe III F6 )] (IV) are prepared by conventional solvothermal synthesis using a EtOH or DMF solution of FeF2, FeF3, and HF (4%) with DABCO (autoclave, 120 °C, 72 h) to explore the composition space diagram of the (Fe 2+, Fe 3+ )‐DABCO‐HFaq chemical system.